The encyclopedia of ancient battles - Whitby, Michael; Sidebottom, Harry (John Wiley & Sons Inc., 2017)
"Focused on both land and sea battle narratives of the classical world, this three-volume reference covers archaic Greece in the eighth century BC to the rise of Islam in the seventh century AD."--Provided by the publisher.